2002
DOI: 10.1901/jaba.2002.35-49
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Relative Efficacy of Three Presentation Methods for Assessing Preferences of Persons With Developmental Disabilities

Abstract: Choices were presented to 9 individuals with developmental disabilities using a two-choice format. Each pair of items, selected based on prior preference assessment, was presented to each participant in three conditions (actual items, pictures of the items, and spoken-name presentation) using a reversal design. The evaluation was conducted using food items, and was then repeated using nonfood items. The participants were also given a test to measure their skills on discrimination tasks ranging in difficulty fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
1
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 11 publications
4
35
1
4
Order By: Relevance
“…Mas é importante lembrar que não apresentar essas habilidades de emparelhamento poderia explicar a falta de correspondência para os outros participantes. Conyers et al (2002) conduziram um estudo para avaliar como as respostas de escolha eram infl uenciadas por modalidades diferentes de estímulos (objetos, fi guras e descrições verbais). Oportunidades de escolha foram apresentadas para nove indivíduos com defi ciência intelectual em uma avaliação de preferência com escolha pareada.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Mas é importante lembrar que não apresentar essas habilidades de emparelhamento poderia explicar a falta de correspondência para os outros participantes. Conyers et al (2002) conduziram um estudo para avaliar como as respostas de escolha eram infl uenciadas por modalidades diferentes de estímulos (objetos, fi guras e descrições verbais). Oportunidades de escolha foram apresentadas para nove indivíduos com defi ciência intelectual em uma avaliação de preferência com escolha pareada.…”
Section: Discussionunclassified
“…AIPs tem sido conduzidas com itens tangí-veis tais como alimentos, brinquedos e materiais instrucionais (Carr et al, 2000;DeLeon & Iwata, 1996;Fisher et al, 1992;Pace et al, 1985;Roane et al, 1998) e com formato alternativos de estímulos, tais como fi guras impressas e descrições verbais dos estímulos (Conyers et al, 2002;Groskreutz & Graff, 2009;Hanley, Iwata, & Lindberg, 1999;Higbee, Carr, & Harrison, 1999).…”
Section: Comparación Entre Preferencias Con Elementos Concretos Y Conunclassified
“…As another example of population-specific findings, paired stimulus preference assessments have been effectively used with individuals with dementia but with different findings about the usefulness of different stimulus modalities (LeBlanc, Cherup, Feliciano & Sidener, 2006;LeBlanc, Raetz, Baker, Strobel, & Feeney, 2008). With consumers with intellectual disabilities and autism, assessments using tangible stimuli produce the most accurate predictions of subsequent reinforcement effects (Conyers et al, 2002;Higbee, Carr, & Harrison, 2002). However, LeBlanc et al (2006) found that an assessment with stimuli presented vocally better predicted subsequent engagement than a tangible format for 2 of the 3 participants with dementia.…”
Section: Task 1: Increase Professional Competence With a New Populationmentioning
confidence: 99%
“…A seguir seguem alguns estudos que se pautaram em mé-todos tradicionais para avaliarem a preferência dos sujeitos experimentais. Conyers et al (2002) conduziram um estudo para avaliar como as respostas de escolha eram infl uenciadas por modalidades diferentes de estímulos (objetos, fi guras e descrições verbais). Foram apresentadas oportunidades de escolha para nove indivíduos com defi ciência intelectual em uma avaliação de preferência com estímulos pareados.…”
unclassified